Contextualizing extrinsic and intrinsic elements of short stories in Indonesian textbooks for primary school level - Saragih, Erikson; Sinaga, Mindo Uli; Simamora, Pesta; Mustika, Samsul (citeus, 2022)
The objective of this study is to look at learning indicators and contextualize extrinsic and intrinsic components in three Indonesian language textbooks for elementary school students. This study employs a qualitative research approach with a content analysis design to attain this purpose. The findings show that textbooks only use one learning indicator for each short story, although intrinsic (themes, characters, and messages) and extrinsic (social values, moral values, cultural values, and religious values) elements have been effectively balanced in the story. short. Although the results of this study do not represent any analysis of short story content in all primary school textbooks, they are highly valuable for students, instructors, and schools when selecting textbooks and short story content to utilize as teaching resources.